FDG PET/CT Findings of Extrarenal Wilms Tumor Originating From the Spinal Cord. (January 2021) - Filizoglu, Nuh; Oksuzoglu, Kevser; Bozkurt, Suheyla; Ozguven, Salih; Erdil, Tanju Yusuf
Abstract : Abstract: Extrarenal Wilms tumor (ERWT) is an extremely rare neoplasm of childhood. It occurs predominantly in retroperitoneum and pelvic or inguinal region without involvement of the kidneys. Although the importance of FDG PET/CT in Wilms tumor is well known, its use in ERWT is limited. Herein, we present FDG PET/CT findings of a 3-year-old girl with a lumbar mass, which was later diagnosed with ERWT.